2009
DOI: 10.1603/029.102.0415
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide-Induced Changes in Protein, RNA, and DNA Contents in Ovary and Fat Body of Female <I>Nilaparvata lugens</I> (Hemiptera: Delphacidae)

Abstract: The widespread use of insecticides is known to cause resurgence in Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) populations, a serious insect pest of rice, Orzya sativa L., crops in Asia. The current study investigated insecticide-induced changes in protein, RNA, and DNA levels in the ovary and fat body of adult female N. lugens. Potted rice plants were sprayed with different concentrations of imidacloprid, triazophos, and detamethrin. The results showed that all three insecticides caused a significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…At 2 days after emergence (2 DAE), the adult females were collected to analyze their gene expression profiles. Many previous investigations demonstrated that third instar nymphs are the key stage to pesticide-stimulated reproduction in BPH 10 11 30 .…”
Section: Methodsmentioning
confidence: 99%
“…At 2 days after emergence (2 DAE), the adult females were collected to analyze their gene expression profiles. Many previous investigations demonstrated that third instar nymphs are the key stage to pesticide-stimulated reproduction in BPH 10 11 30 .…”
Section: Methodsmentioning
confidence: 99%
“…In BPH, triazophos also could increase the contents of fat body protein and ovarian protein. 21,22,24,25,30 In addition, exposure to triazophos increased the titers of circulating juvenile hormone, the contents of unfractionated lipids and soluble sugar that supported reproduction of planthoppers. 19 Thus, triazophos was generally considered to be a classic resurgence-inducing insecticide.…”
Section: Wileyonlinelibrarycom/journal/psmentioning
confidence: 98%
“…The stimulatory effects of sub‐lethal concentrations of triazophos, deltamethrin and imidacloprid have been documented for several rice pests. Previous studies have demonstrated that sub‐lethal concentrations of triazophos (10, 20, 40 and 80 ppm) and deltamethrin (1, 3, 6 and 12 ppm) stimulated the fecundity of N. lugens . A sub‐lethal dose (22.5 g a.i.…”
Section: Discussionmentioning
confidence: 99%